RELIGIOUS PROPAGANDA AS HEGEMONY STRATEGY DEPICTED IN AGORA (2009) - Setiaji, Purwoko Budhi; Zein, Afrizal; Naqi, Ali; Jalatirani, Dominika Jenetaugusta (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2018)
This paper entitled âReligious Propaganda as Hegemony Strategy Depicted in Agora (2009)â aims to find out the hegemony occurred in Agora movie that is reflected through religious propaganda. In conducting the research, the researcher uses the theory of hegemony by Antonio Gramsci. The data collection was based on the dialogue of the movie, which then supported by books, journals, and articles depicting the hegemony and the social setting of the movie. In conducting the research, the researchers found that the hegemony depicted in the Agora movie are reflected in the religious propaganda in the form of condemnation towards other religion and the preaching of the Christianity itself.